Family jewels [compact disc, unabridged] - Woods, Stuart (Woods, Stuart. Stone Barrington novel, 2016)
Stone Barrington's newest client seems to be a magnet for trouble. A poised lady of considerable wealth, she's looking for help discouraging the attentions of a tenacious gentleman. But no sooner does Stone fend off the party in question than his client becomes involved in two lethal crimes. With suspects aplenty, Stone must probe deep into his client's life to find the truth, and he discovers that the heart of the mystery may be a famous missing piece of history, a stunningly beautiful vestige of a bygone era. It's a piece with a long and storied past and untold value ... the kind of relic someone might kill to obtain.